A study on common clinical pattern of presentation of skin and hair changes in nutritional deficiencies associated with dietary fallacies in children 1 to 5 years of age - Kumar D., Pavan (International Journal of Contemporary Pediatrics, 2018)
Background: Dermatological problems constitute atleast 30% of all outpatient visits to the paediatricians and 30% of all visits to dermatologists involving children. Skin diseases in the paediatric age group can be transitory or chronic and recurrent. The chronic dermatoses are associated with significant morbidity and psychological impact. Skin disorders caused by deficiency generally, or less often by an excess of one or more nutrients is called nutritional dermatoses. The objective of the present study was to assess the common clinical pattern of presentation of skin and hair changes in nutritional deficiencies associated with dietary fallacies in children 1 to 5 years of age. Methods: A hospital based cross sectional study consisting of all children between the age group of 1 to 5 years with Nutritional skin and hair lesions diagnosed with clinical examination in the OPD of the Pediatric Department were included in the study from the month of November 2012 to October 2013. A minimum sample size of 100 children is required for this study. However, author included 150 children. Results: In the present study, maximum numbers of children were in the age group of 12 – 24 months, 33.33 % (50) of study subjects. The proportion of males 58.00% (87) is higher than females 42.00% (63). Majority of children belonged to Class IV 60.66% (91) socioeconomic status. 76.00% (114) of children fall in the group of under nutrition and this can be attributed to the associated Dietary fallacies of 73.33% (110) children as causative factor. Nutritional anemia associated pallor and sparse hair were the common finding among all other nutritional deficiencies. Conclusions: Lower socio- economic condition and dietary fallacies were the two most causative factors which had an adverse effect on nutritional status of child causing dermatoses. In the present study, majority of children had nutritional anemia, vitamin A deficiency and vitamin B12 deficiency associated dermatoses with overlapping of the clinical features because of complex interlinking of different dietary factors.